Nilai Kearifan Lokal Ritual Moritana dalam Kepercayaan Marapu di Sumba Barat Daya - Pati, Yohanes Ronaldo Kowak; Panda, Herman Punda; Naif, Oktovianus (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2024)
Indigenous beliefs that live in many places in Indonesia have intangible wealth in the form of local wisdom. This local wisdom is manifested, among other things, through rituals involving many community members. This research aims to highlight local wisdom values from the Moritana ritual of the Marapu belief in the island of Sumba. The research method used is qualitative research which includes field research and literature review. The research results show the value of local wisdom of the local community through the Moritana ritual which includes religious, ethical and social values. These values can contribute to strengthening social and religious life for both local communities and the wider community.